Treatment as Prevention: Characterization of Partner Infections in the HIV Prevention Trials Network 052 Trial - Susan H. Eshleman (2018)
Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved. HIV Prevention Trials Network 052 demonstrated that antiretroviral therapy (ART) prevents HIV transmission in serodiscordant couples. HIV from index-partner pairs was analyzed to determine the genetic linkage status of partner infections. Forty-six infections were classified as linked, indicating that the index was the likely source of the partner's infection. Lack of viral suppression and higher index viral load were associated with linked infection. Eight linked infections were diagnosed after the index started ART: 4 near the time of ART initiation and 4 after ART failure. Linked infections were not observed when the index participant was stably suppressed on ART.